O método dos elementos de contorno com interpolação direta aplicado à solução de problemas escalares funcionais em duas dimensões - Barcelos, Hercules de Melo (2019)
Recently, major challenges have emerged with the advances of modern engineering, and with this, the search for more elaborate model solutions becomes necessary. In this context, the numerical formulations to treat domain integrals present in these models